Digital Soveregnity: Woman Soveregnity in Digital Space Discourse in Banten - Ramadhan, Gilang; Nurrohman, Bayu (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
In the current era of digital technology disruption, social media now allows people or groups to interact with each other. The gender movement is one of many movements that have developed into a platform for women's communities and movements. With the advent of the internet and social media, this gender movement continues to fight through social media, such as @rpa_banten and @suluhperempuanserang accounts. Using a qualitative content analysis method, this study investigates the gender movement on the Instagram accounts @rpa_banten and @suluhperempuanserang. According to the Instagram profile posts and views of @rpa_banten and @suluhperempuanserang, these accounts represent a gender movement that fights against sexual violence, fights legal injustice for victims of sexual violence, and supports the adoption of the Permendikbud and RUU PKS as the legal framework for sexual violence in the country. Digital litracy is needed to expand the impact of campaigns voiced by the gender movement to promote women's sovereignty in the digital realm.